Decoding of FFH/FSK system with diversity-combining receiver over composite interference channel - Sun, Xueyang (Nanyang Technological University, 2023)
Fast frequency-hopped (FFH) spread-spectrum (SS) systems have gained popularity in recent years for both commercial and military applications. However, fading and interference effects will impair the Bit-Error Rate (BER) performance. In this Final Year Report, the simulation of BER performance and investigation of FFH/FSK systems utilizing various diversity combining techniques over composite interference channels will be carried out using MATLAB software. In addition, the system uses frequency hopping to reduce the impact of fading and interference and employs a diversity-combining receiver to lower the bit error rate and increase the signal-to-noise ratio. The system’s performance under different communication channel conditions, including additive white Gaussian noise (AWGN), Rayleigh and Rician fading channel. As well as the composite interference channel which is Partial Band Noise Interference (PBNI) will be analysed and discussed. The diversity-combining receiver provides significant improvements in the system's performance, particularly in the presence of PBNI. These results finding leads to a greater comprehension of the advantages of using diversity combining for communication systems operating in challenging interference environments.